Multifunctions of Polymer Nanocomposites: Environmental Remediation, Electromagnetic Interference Shielding, And Sensing Applications. Issue 2 (9th January 2020) - Wei, Huige; Wang, Hui; Li, Ang; Cui, Dapeng; Zhao, Zinian; Chu, Liqiang; Wei, Xin; Wang, Lin; Pan, Duo; Fan, Jincheng; Li, Yingchun; Zhang, Jiaoxia; et al.
Abstract: Polymer nanocomposites (PNCs), i. e . nanofillers dispersed in a polymer matrix, have become a prominent area of current research promoted by rapid developments in the polymer science and nanotechnology. As a promising alternative to conventional composites which are reinforced with micro‐scale fillers, PNCs exhibit substantially improved overall performance and simplified processing at much lower nanofiller loadings. PNCs have great potentials for a broad range of applications, e. g . environmental remediation, energy storage/conversion, transportation, and national defense. In this regard, the most recent advances in PNCs for the environmental remediation, electromagnetic interference (EMI) shielding and sensing & actuation applications are presented. Challenges and perspectives of PNCs are also discussed. Abstract : Polymer nanocomposites have become a prominent area of current research which exhibit substantially improved overall performance and simplified processing compared to conventional polymer composites. The most recent advances in PNCs for the environmental remediation, electromagnetic interference (EMI) shielding and sensing & actuation applications are presented. Challenges and perspectives of PNCs are also discussed.